Sirt2 in the Spinal Cord Regulates Chronic Neuropathic Pain Through Nrf2-Mediated Oxidative Stress Pathway in Rats - Zhao, Mengnan; Zhang, Xiaojiao; Tao, Xueshu; Zhang, Bohan; Sun, Cong; Wang, Pinying; Song, Tao (Frontiers in Pharmacology, 2021)
Reduction in Nrf2-mediated antioxidant response in the central nervous system plays an important role in the development and maintenance of neuropathic pain (NP). However, the mechanisms regulating Nrf2 activity in NP remain unclear. A recent in vitro study revealed that Sirt2, a member of the sirtuin family of proteins, affects antioxidant capacity by modulating Nrf2 activity. Here we examined whether central Sirt2 regulates NP through Nrf2-mediated oxidative stress pathway. In a rat model of spared nerve injury (SNI)-induced NP, mechanical allodynia and thermal hyperalgesia were observed on day 1 and up to day 14 post-SNI. The expression of Sirt2, Nrf2 and its target gene NQO1 in the spinal cord in SNI rats, compared with sham rats, was significantly decreased from day 7 and remained lower until the end of the experiment (day 14). The mechanical allodynia and thermal hyperalgesia in SNI rats were ameliorated by intrathecal injection of Nrf2 agonist tBHQ, which normalized expression of Nrf2 and NQO1 and reversed SNI-induced decrease in antioxidant enzyme superoxide dismutase (SOD) and increase in oxidative stress marker 8-hydroxy-2'-deoxyguanosine (8-OHdG) in the spinal cord. Moreover, intrathecal injection of a recombinant adenovirus expressing Sirt2 (Ad-Sirt2) that upregulated expression of Sirt2, restored expression of Nrf2 and NQO1 and attenuated oxidative stress in the spinal cord, leading to improvement of thermal hyperalgesia and mechanical allodynia in SNI rats. These findings suggest that peripheral nerve injury downregulates Sirt2 expression in the spinal cord, which inhibits Nrf2 activity, leading to increased oxidative stress and the development of chronic NP.